Viridicatol from the Deep‐Sea‐Derived Fungus Alleviates Bone Loss by Targeting the Wnt/SHN3 Pathway - Chun‐Lan Xie; Shang‐Hui Ye; Yu‐Ting Yue; Bao‐Hong Shi; Jing‐Ping Xu; Lian‐Jie Li; Zheng‐Biao Zou; Matthew B. Greenblatt; Na Li; Xian‐Wen Yang; Ren Xu (Advanced Science)
Abstract As an enticing bone anabolic target, short‐term inhibition of Schnurri‐3 (SHN3) resulted in high‐bone mass due to augmented osteoblast activity. However, no studies are conducted to identify natural products targeting SHN3 inhibition. Herein, a screening strategy for the discovery of marine compounds that facilitate osteoblast differentiation by targeting SHN3 silencing is presented. One leading quinolinone alkaloid, viridicatol (VDC), isolated from deep‐sea‐derived fungus, vigorously promotes osteogenic differentiation via the Wnt/SHN3 signaling pathway in osteoblasts, thereby preventing osteoporosis while enhancing bone‐fracture healing in a mouse model. Subsequently, the SDSSD (Ser, Asp, Ser, Ser, Asp) is further employed to engineer bone‐targeting nanovesicles (BT‐NVs) for the optimal delivery of VDC to osteoblasts, which mitigates the bone loss observed in a severe osteogenesis imperfecta model. Hence, these results initially uncover a promising marine natural product, VDC, targeting the Wnt/SHN3 pathway for the treatment of bone loss and highlighting its translational potential in clinical applications.